Anticancer Approach Inspired by the Hepatotoxic Mechanism of Pyrrolizidine Alkaloids with Glycosylated Artificial Metalloenzymes. (23rd September 2022) - Kurimoto, Michitaka; Chang, Tsung‐che; Nishiyama, Yoshitake; Suzuki, Takehiro; Dohmae, Naoshi; Tanaka, Katsunori; Yokoshima, Satoshi
Abstract: Metabolic oxidation of pyrrolizidine alkaloids (PAs) from herbal and dietary supplements by cytochrome P450 produces dehydro‐PAs (DHPs), which leads to toxicities. A highly reactive cation species generated from the active pyrrole ring of DHPs readily reacts with various cellular components, causing hepatotoxicity and cytotoxicity. Inspired by PA‐induced hepatic damage, we developed a therapeutic approach based on a cyclization precursor that can be transformed into a synthetic DHP under physiological conditions through gold‐catalyzed 5 ‐ endo ‐ dig cyclization using a gold‐based artificial metalloenzyme (ArM) instead of through metabolic oxidation by cytochrome P450. In cell‐based assays, the synthesis of the DHP by a cancer‐targeting glycosylated gold‐based ArM substantially suppressed cell growth of the targeted cancer cells without causing cytotoxicity to untargeted cells, highlighting the potential of the strategy to be used therapeutically in vivo. Abstract : Metabolic oxidation of pyrrolizidine alkaloids (PAs) by cytochrome P450 produces dehydro‐PAs (DHPs), which leads to toxicities. We developed a therapeutic approach, in which a precursor is transformed into a synthetic DHP via 5 ‐ endo ‐ dig cyclization catalyzed by a gold‐based artificial metalloenzyme (ArM). In cell‐based assays, the synthesis of the DHP by a glycosylated ArM suppressed cell growth of targeted cancer cells.